Role of inducible nitric oxide (iNOS) and nitrosative stress in regulating sex differences in secondary lymphedema - Campbell, Adana-Christine; Kuonqui, Kevin G.; Ashokan, Gopika; Rubin, Jonathan; Shin, Jinyeon; Pollack, Bracha L.; Roberts, Arielle; Sarker, Ananta; Park, Hyeung Ju; Kataru, Raghu P.; Barrio, Andrea V.; Mehrara, Babak J. (Frontiers in Physiology, 2024)
Secondary lymphedema is a common complication following surgical treatment of solid tumors. Although more prevalent in women due to higher breast cancer rates, men also develop lymphedema, often with more severe manifestations. Despite these differences in clinical presentation, the cellular mechanisms underlying sex differences are poorly understood. Previous studies have shown that inducible nitric oxide synthase (iNOS) expression by inflammatory cells is an important regulator of lymphatic pumping and leakiness in lymphedema and that lymphatic endothelial cells are highly sensitive to nitrosative stress. Based on this rationale, we used a mouse tail model of lymphedema to study the role of nitric oxide in sex-related differences in disease severity. Consistent with clinical findings, we found that male mice have significantly worse tail edema and higher rates of tail necrosis compared with female mice following tail skin/lymphatic excision (p = 0.001). Our findings correlated with increased tissue infiltration of iNOS + inflammatory cells, increased iNOS protein expression, and increased nitrosative stress in male mouse lymphedematous skin tissues (p < 0.05). Importantly, transgenic male mice lacking the iNOS gene (iNOS-KO) displayed markedly reduced swelling, inflammation, and tissue necrosis rates, whereas no differences were observed between wild-type and iNOS-KO female mice. Overall, our results indicate that iNOS-mediated nitric oxide production contributes to sex-based differences in secondary lymphedema severity, emphasizing the need to consider sex as a biological variable in lymphedema research.